Strategi Guru Dalam Membina Karakter Disiplin Bagi Siswa Kelas V Sekolah Dasar Negeri 009 Kepau Jaya - Riki Apriadi; Dea Mustika (Universitas Negeri Padang, 2023)
The purpose of this study was to describe the teacher's strategy in instilling the character of discipline in class V students and describe what were the obstacles to the teacher's strategy in instilling the character of discipline in class V students at SDN 009 Kepau Jaya. This research method uses a case study approach in the form of observation, interviews and documentation. Testing the validity of the research data was carried out by technical triangulation, time triangulation, and source triangulation. Source triangulation was carried out by selecting informants from Class V.A homeroom teachers and students at SD Negeri 009 Kepau Jaya. Based on the results of the study it can be concluded that the disciplinary character-building activities carried out by the teacher have been running optimally for students. Discipline character-building activities are carried out with several indicators, namely instilling exemplary attitudes, giving rewards, carrying out habituation and imposing sanctions.Strategi Guru Dalam Membina Karakter Disiplin Siswa Kelas V.A di Sekolah Dasar Negeri 009 Kepau Jaya